(untitled) - Steiner, Hans (San Francisco, CA, 2004)
The Handbook of Mental Health Interventions in Children and Adolescents is an essential guide for mental healthcare professionals to the theory and practice of mental health treatment for children up to age nineteen. Written by a panel of the best-known names in the field, this systematic and comprehensive resource includes the most current information on developmental science as it pertains to treatment, psychopharmacology, psychotherapy, sociotherapy, and the integration of treatments.
Keywords: Child mental health services,Child psychotherapy,Adolescent psychotherapy